PE#01 Price escalation for internal electrification works rev.03 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the resubmission of revised price for internal electrification works of BRACU new campus project.